Principles of pediatric lupus nephritis in a prospective contemporary multi-center cohort. (September 2021) - Vazzana, Kathleen M; Daga, Ankana; Goilav, Beatrice; Ogbu, Ekemini A; Okamura, Daryl M; Park, Catherine; Sadun, Rebecca E; Smitherman, Emily A; Stotter, Brian R; Dasgupta, Abhijit; Knight, Andrea M; Hersh, Aimee O; et al.
Lupus nephritis (LN) is a life-threatening manifestation of systemic lupus erythematosus (SLE) and is more common in children than adults. The epidemiology and management of childhood-onset SLE (cSLE) have changed over time, prompting the need to reassess expected outcomes. The purpose of this study is to use the Childhood Arthritis and Rheumatology Research Alliance (CARRA) prospective registry to validate historical principles of LN in a contemporary, real-world cohort. After an extensive literature review, six principles of LN in cSLE were identified. The CARRA registry was queried to evaluate these principles in determining the rate of LN in cSLE, median time from cSLE diagnosis to LN, short-term renal outcomes, and frequency of rituximab as an induction therapy. Of the 677 cSLE patients in the CARRA registry, 32% had documented LN. Decline in kidney function was more common in Black cSLE patients than non-Black patients ( p = 0.04). Black race was associated with worse short-term renal outcomes. In short-term follow up, most children with LN had unchanged or improved kidney function, and end stage kidney disease (ESKD) was rare. Ongoing follow-up of cSLE patients in the CARRA registry will be necessary to evaluate long-term outcomes to inform risk, management, and prognosis of LN in cSLE.